Treatment indicators influence speech therapy discharge time - Marianna Avelino Tavares; Patrícia Pupin Mandrá; Thaís Cristina da Freiria Moretti; Carla Manfredi dos Santos; Letícia Brunelli Wolf; Maysa Luchesi Cera (CoDAS, 2021)
ABSTRACT Purpose To compare the treatment time for acquired neurological disorders of communication and the reason for discharge of users of a medium complexity care service for two periods: before and after implementation of treatment indicators. Methods A retrospective cohort study was carried out involving the analysis of medical records of users of the Adult Language Sector of the Speech and Hearing Therapy Service of the Integrated Rehabilitation Center, seen before and after treatment indicators implementation. Results 129 electronic medical records of users who remained under treatment until discharge from speech therapy in the two studied periods were analyzed. The mean duration of speech therapy for these users was 10.9 months for the first period and 7.8 months for the second period. After implementation of the indicators with regular reassessments, 72 out of the 89 users continued with treatment. There was a statistically significant difference in the therapy average time and reason for discharge before and after treatment indicators implementation. Conclusion After treatment indicators implementation, there was a reduction of the average speech therapy treatment time for communication disorders and an increase of speech therapy discharge percentage of users seen in a Brazilian service of medium complexity.